Alliances for Knowledge: A Strategy for Building the Future of University in the Digital Society - Garito, Maria Amata (Advances in Social Sciences Research Journal, 2023)
This paper investigates the transformative potential of the Internet in redefining the structure and purpose of traditional universities. It underscores the challenges posed by technology, globalization, socio-economic development, and evolving training needs, and highlights the importance of reinvention for universities to remain relevant. It argues that universities must transition from a conventional pedagogical model to one that fosters collaborative learning, enabled by digital technologies, and provides a platform for the exchange of knowledge that transcends geographical boundaries. Through the case study of UNINETTUNO, the paper elucidates the implementation of an open, inclusive, and flexible educational model offering courses in multiple languages, fostering international relations and mutual understanding. Further, it advocates the establishment of a global network of public and private universities, emphasizing shared knowledge, resources, and mobility of faculty and students. The paper concludes with a compelling call to democratize access to knowledge, promoting the use of the internet to create a worldwide, open system of teaching and learning. This vision challenges the status quo and paves the way for an educational future where learning truly knows no bounds.